The seed of humanism: morality and fundamental ontology in Heidegger (2014)
Throughout the preparatory analysis of human existence (Dasein), Heidegger holds the firm conviction of the moral neutrality of the phenomenological interpretation. However, in determining the temporal sense of care (Sorge) as the being of Dasein, Heidegg